2020
DOI: 10.26452/ijrps.v11i2.2072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro antioxidant and anti-atherogenic properties of selected Siddha polyherbal decoctions

Abstract: This research work explains the antioxidant and anti-atherogenic effects of selected Siddha polyherbal decoctionssuch as Nilavembukudineer, Kabasurakudineer, NotchikudineerandAdathodaikudineer. Even though all the above decoctions have been used for fever, cold, cough, bronchitis, dysphonea and body pain in Siddha system of medicine, their antioxidant and anti-atherogenic properties were notinvestigated scientifically.We have analyzed the polyphenolic content, antioxidant and anti-atherogenic properties of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In this toxicity study Peripheral blood mononuclear cells (PBMC) were used to which different concentrations of the preparation were added. The studied sample was not toxic to PMBC at the selected concentration range which was also found to be advantageous for its anti atherogenic potential suggesting that the results of the current study are in concordance with literature [58]. The results of the current study showed that the Abies webbiana ethanolic extract based preparation of mouthwash possessed cytotoxic effect on nauplii and it was found that the nauplii alive was directly proportional to the concentrations except in the concentration of 40μl.…”
Section: Bar Graph With Error Bar Shows the Cytotoxic Activity Of Abi...supporting
confidence: 87%
“…In this toxicity study Peripheral blood mononuclear cells (PBMC) were used to which different concentrations of the preparation were added. The studied sample was not toxic to PMBC at the selected concentration range which was also found to be advantageous for its anti atherogenic potential suggesting that the results of the current study are in concordance with literature [58]. The results of the current study showed that the Abies webbiana ethanolic extract based preparation of mouthwash possessed cytotoxic effect on nauplii and it was found that the nauplii alive was directly proportional to the concentrations except in the concentration of 40μl.…”
Section: Bar Graph With Error Bar Shows the Cytotoxic Activity Of Abi...supporting
confidence: 87%
“…As such, the Siddha system of medicine had been in use for infectious diseases particularly for treating ammai noi ( pox viral infections ) and akki noi (herpes infections) diseases for more than thousands of years [ 28 ]. The herbs as indicated in several Siddha medicine-based formulations have been documented to have multiple effects including that of antiviral activity [ 29 ]. Some of these herbal constituents work directly on the therapeutic targets, while others potentially enhance the bioavailability or counteract drug toxicity of the medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnopharmacological actions of these fifteen ingredients demonstrated that KSK having anti-inflammatory, antipyretic, analgesic, anti-viral, anti-bacterial, anti-fungal, anti-oxidant, hepatoprotective, anti-diabetic, anti-asthmatic, immunomodulatory, anti-diarrheal and anti-oxidant activities ( Thillaivanan et al, 2015 ). Recent studies on KSK showed its significant antiviral effect as well as its efficacy against SARS-CoV-2 through the In-silico method, Immunomodulatory action, thrombolytic activity, antioxidant and anti-atherogenic activity method ( Shree Devi et al, 2021 ; Vincent et al, 2020 ; Sathiyarajeswaran et al, 2020 ; Rajalakshmi et al, 2020 ). In Silico computational screening, Molecular docking and Clinical studies on the anti-viral effects of phytoconstituents ( Table 1 ) present in KSK has been well established by various studies ( Kiran et al, 2020 ; Vincent et al, 2020 ; Maideen, 2021 ).…”
Section: Introductionmentioning
confidence: 99%